An Overview of Human Resource (HR) Needs Based on WISN Theory at The Central Sterile Supply Department (CSSD) of PKU Muhammadiyah Gamping Hospital - Muzayyanah Muzayyanah*; Abdul Choliq Hidayat (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to evaluate human resource (HR) needs in the Central Sterile Supply Department (CSSD) of PKU Muhammadiyah Gamping Hospital using the Workload Indicator of Staff Need (WISN) method. This method is used to measure the comparison between the amount of energy required and the amount of energy available to handle the workload in the sterilization unit. The data used in this study includes information about the number of sterilization procedures, the time required for each procedure, and the number of sterilization personnel available. The analysis was carried out using the WISN formula to calculate the ratio of sterilization personnel requirements. The results of the research show that the WISN ratio for the need for sterilization personnel at CSSD PKU Muhammadiyah Gamping Hospital is 0.6, indicating that there is a shortage of sterilization personnel. This indicates that the number of sterilization personnel currently available needs to be increased to handle the existing workload. In order to achieve a state of balance between the number of personnel available and those required, research recommends the addition of 7 sterilization personnel. This addition is expected to increase the efficiency and quality of the sterilization process, as well as reduce the risk of delays and disruptions in health services. This research provides an important contribution to the planning and management of human resources at CSSD PKU Muhammadiyah Gamping Hospital, as well as providing a strong basis for decision-making regarding additional sterilization personnel to improve the quality and safety of health services.